2009
DOI: 10.1080/01443610802712900
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal measurement of cervical length in the prediction of successful induction of labour

Abstract: A total of 100 women with gestational ages of 34-42 weeks requiring induction of labour were consecutively recruited in a prospective study at the Medical College and Hospital, Baroda, India. The aim of this study was to determine the value of transvaginal measurement of cervical length in the prediction of successful vaginal delivery within 24 h. Induction of labour was carried out with Tab Misoprostol (25 microg). A Bishop's score and sonographic cervical assessment were performed prior to induction. Univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…However further analysis using Kaplan-Meier survival curves demonstrated that cervical length was a better predictor compared to Bishop score. Similar results were published by Maitra et al and Sharma et al, both quoting a cervical length cut-off of less than 30mm, as a better predictor of successful induction compared with Bishop score [ 10 , 14 ]. A Cochrane review in 2015 reported no clear difference between cervical length and Bishop score in predicting outcome of labour induction [ 6 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However further analysis using Kaplan-Meier survival curves demonstrated that cervical length was a better predictor compared to Bishop score. Similar results were published by Maitra et al and Sharma et al, both quoting a cervical length cut-off of less than 30mm, as a better predictor of successful induction compared with Bishop score [ 10 , 14 ]. A Cochrane review in 2015 reported no clear difference between cervical length and Bishop score in predicting outcome of labour induction [ 6 ].…”
Section: Discussionsupporting
confidence: 86%
“…Hence scoring may vary according to each clinician. In addition, cervical changes such as funnelling at internal os and cervical length may be difficult to assess in closed cervical os [ 10 ]. For these reasons, many sought to find other methods of cervical assessment which may be more objective and reproducible in predicting the success of labour induction.…”
Section: Introductionmentioning
confidence: 99%
“…the active phase within the specified time, which is consistent with previous research reports. [4][5][6] However, we also found that when CL was considered as an independent predictive variable, it only had a good value for predicting whether patients could enter the active phase within 18 h but had a low predictive value for other outcomes in total samples. In particular, it had no significant effect on the outcome of undergoing vaginal delivery within 24 h whether in total samples or primiparas, indicating that the predictive value of this single indicator is limited.…”
Section: Discussionmentioning
confidence: 73%
“…[14] Another study from India reported that cervical length measurement by transvaginal ultrasonography is an independent predictor of successful labour induction. [15] Another study reported that transvaginal ultrasonography was less painful than digital vaginal exams and that both Bishops score (>=5) and cervical length (>20mm) measures were independent predictors of the need for caesarean delivery. [16] A metaanalysis reported that cervical elastography and cervical length (diagnostic odds ratio 3.35, 95% CI: 1.95, 5.77) measurements are similarly reliable in the prediction of successful labour.…”
Section: Marian Et Al; Assessing Cervical Length By Transvaginal Ultrmentioning
confidence: 99%